Analisis efektifitas pengelolaan sampah organik kering dengan metode komposting pada taman kota - Hutagalung, Dodi Saputra; Naria, Evi; Tumanggor, Winni R.E. (TROPHICO: Tropical Public Health J., 2023)
Every day was produced dry organic waste from Ahmad Yani Park Medan City accumulates in the Tanjung Marelan Landfills. The average waste generation reaches 0.797 m3/day. Continuous accumulation of dry organic waste can endanger the environment and public health. The purpose of the study was to examine how effective composting is as a method of managing dry organic waste in a city park. This research is quasi-experimental, research object was 5 kg of dry organic waste, four repetitions with three composting methods, namely Barkley, Composting Bag, and Takakura. The research location is Taman Ahmad Yani, Medan City. The study used univariate analysis and bivariate analysis with ANOVA one-way test and Bonferroni Test. Based on the results of the study, the composting time for dry organic waste in the three composting methods applied lasted 19-25 days. The results of the study, the composting time for dry organic waste is 19-25 days. The compost maturity characteristics same for each composting method, namely blackish brown in color, earthy smell and texture, pH 7,0-7,2, and temperature <30oC according to SNI Compost Quality Standard: 19-7030-2004. Based on the results of the ANOVA test p-value=0,010 and Bonferroni Test, showed that there was a significant difference in the decrease the volume of dry organic waste in each treatment after composting. The reduction of dry organic waste reached 67% -75.75%. The application of the composting method is an effective solution as a dry organic waste management method to reduce the accumulation of dry organic waste in landfills.